Serat Ngalamating Kucing Mitos Kucing dalam Budaya Jawa - Mirya A Mirya A (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This study aims to reveal the myth of cats in Javanese culture on Serat Ngalamating Kucing. Material object of this research  Serat Ngalamating Kucing.  In various nations of the world, cats are special animals. It is also found in Javanese culture. One indication that shows the specialty of a cat is the text of the old manuscript entitled Serat Ngalamating Kucing. The results showed various types of cats are good or bad to keep. Other than that, also told about the behavior and fur of a cat that signifies something for humans.  According to Javanese people, a good cat is a bundhel or blunt. A good cat is maintained will add good if the tail bundhel or blunt.